Neonatal Face Mosaic: An areas-of-interest segmentation method based on 2D face images - Domingues, Pedro Henrique Silva; Silva, Renan Martins Mendes da; Orra, Ibrahim Jamil; Cruz, Matheus Elias; Heiderich, Tatiany Marcondes; Thomaz, Carlos Eduardo (Anais do Workshop de Visão Computacional (WVC); 2021: Anais do XVII Workshop de Visão Computacional, 2021)
The daily life of preterm babies may be involved with long exposure to pain, causing problems in the development of the nervous system. In this context, an on-going area of research is the scientific development of image-based automatic pain detection systems based on several techniques, from anatomical measurements to artificial intelligence, they have generally two main issues: the categorization of the most relevant facial regions for identifying neonatal pain and the practical difficulty related to the presence of artifacts obstructing parts of the face. This paper proposes and implements an areas-of-interest automatic segmentation method that allows the creation of a novel dataset containing crops of neonatal faces relevant for pain classification, labelled by areas-of-interest and pain status. Moreover, we have also investigated the use of similarity matching techniques to compare each area-of-interest to the corresponding one extracted from a prototype face with no occlusion.t